2009
DOI: 10.1007/s00105-009-1840-z
|View full text |Cite
|
Sign up to set email alerts
|

Beeinflusst die Verdünnung das kosmetische Ergebnis von BoNT/A?

Abstract: Complex-protein-free botulinum neurotoxin type A in both dilutions effectively reduced severity of glabellar lines. There was no statistically significant difference in efficacy between the two dilutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…8,9 Another comparative study involving 40 patients used 5 injection points of 5 U incobotulinumtoxinA in either 0.125 or 0.2 mL per injection point to treat glabellar lines and found no difference in response rate between the 2 treatment groups. 10 …”
Section: Discussionmentioning
confidence: 99%
“…8,9 Another comparative study involving 40 patients used 5 injection points of 5 U incobotulinumtoxinA in either 0.125 or 0.2 mL per injection point to treat glabellar lines and found no difference in response rate between the 2 treatment groups. 10 …”
Section: Discussionmentioning
confidence: 99%
“…Despite a fivefold difference in concentration between the two dilutions, no significant differences in efficacy or duration of effect were observed . A study of two different dilutions of BoNTA‐INCO in the glabellar lines also found no significant clinical differences in results …”
Section: Practical Bonta Injection Strategy Considerationsmentioning
confidence: 96%
“…Blümel and colleagues confirmed in an animal study that there was no neutralizing antibody formation against BoNTA, even after administration of high doses at short injection intervals 16,17 . There are now also a number of clinical studies published examining the aesthetic use of BoNTA, including treatment of periorbital lines 18–22 …”
mentioning
confidence: 99%
“…16,17 There are now also a number of clinical studies published examining the aesthetic use of BoNTA, including treatment of periorbital lines. [18][19][20][21][22] Comparative studies between BoNTA and BTXCo have only been performed for neurological conditions such as torticollis and blepharospasm. Five clinical trials (phase I-III) with more than 800 patients have indicated high efficacy and good tolerability for BoNTA and BTXCo at a dose ratio of 1:1.…”
mentioning
confidence: 99%